Respuesta :

-3x + `1 +6x =- 2x+16
-3x+6x+2x =16-1
5x=15 x=3
Simplify the equation. All the negative signs are making my head whirl, and to answer that equation and find the value of x, you'd have to simplify it until it can't be simplified any further. So the equation is :

-3x - ( - 1 - 6x ) = -2 ( x - 8)

Simplify the negative signs. Negative and a negative make a positive. Let's simplify this all the way through.

-3x + 1 + 6x = -2x + 18
3x + 1 = -2x + 18

Now that we've simplified it as much as we possibly could, we try and isolate the variable by subtracting and adding what's necessary. In other words, inverse operations.

3x = -2x + 17

So I decided to subtract one from each side, leaving the side with 3x with nothing but the 3. Now, we're going to subtract -2x, because there's more than one number with an x value attached.

5x = 17

We divide to isolate the variable. 17 ÷ 5 = 3.4.

x = 3.4